Two-probe STM experiments at the atomic level. (5th October 2017) - Kolmer, Marek; Olszowski, Piotr; Zuzak, Rafal; Godlewski, Szymon; Joachim, Christian; Szymonski, Marek
Abstract: Direct characterization of planar atomic or molecular scale devices and circuits on a supporting surface by multi-probe measurements requires unprecedented stability of single atom contacts and manipulation of scanning probes over large, nanometer scale area with atomic precision. In this work, we describe the full methodology behind atomically defined two-probe scanning tunneling microscopy (STM) experiments performed on a model system: dangling bond dimer wire supported on a hydrogenated germanium (0 0 1) surface. We show that 70 nm long atomic wire can be simultaneously approached by two independent STM scanners with exact probe to probe distance reaching down to 30 nm. This allows direct wire characterization by two-probe I – V characteristics at distances below 50 nm. Our technical results presented in this work open a new area for multi-probe research, which can be now performed with precision so far accessible only by single-probe scanning probe microscopy (SPM) experiments.